CESM1 2015 Cold Blob Sensitivity Experiments - Maroon, Elizabeth (10787651) (2021)
CESM1-DPLE Hindcast Sensitivity Experiments from Maroon et al. (2021) The files in this repository include CESM sensitivity experiment output shown in Maroon et al. (2021). Descriptions of the protocols for each of the experiments can be found in the paper. Each individual compressed file here corresponds to one of the sensitivity experiments. Individual netcdf files are in standard CESM1 time series format using CESM1 naming convention. Each included variable has its own folder and inside there is one netcdf file for each ensemble member. Please contact the authors if you have any difficulty opening the files or figuring out which files go with which sensitivity experiments (emaroon@wisc.edu). Maroon, E. A., Yeager, S. G., Danabasoglu, G., & Rosenbloom, N. (2021). Was the 2015 North Atlantic subpolar cold anomaly predictable?, Journal of Climate, https://doi.org/10.1175/JCLI-D-20-0750.1